Immune Cells Gate White Adipose Tissue Expansion - Cox, Aaron R (Endocrinology, 2019)
The immune system plays a critical role in white adipose tissue (WAT) energy homeostasis and, by extension, whole-body metabolism. Substantial evidence from mouse and human studies firmly establishes that insulin sensitivity deteriorates as a result of subclinical inflammation in the adipose tissue of individuals with diabetes. However, the relationship between adipose tissue expandability and immune cell infiltration remains a complex problem important for understanding the pathogenesis of obesity. Notably, a large body of work challenges the idea that all immune responses are deleterious to WAT function. This review highlights recent advances that describe how immune cells and adipocytes coordinately enable WAT expansion and regulation of energy homeostasis.